Unraveling Doping Capability of Conjugated Polymers for Strategic Manipulation of Electric Dipole Layer toward Efficient Charge Collection in Perovskite Solar Cells - Park, Jaehong; Yoon, Sang Eun; Lee, Jongmin; Whang, Dong Ryeol; Lee, Sang Yeon; Shin, So Jeong; Han, Ji Min; Seo, Hyungtak; Park, Hui Joon; Kim, Jong H.; Kim, Bong Gi (Advanced Functional Materials, 2020)
Developing electrical organic conductors is challenging because of the difficulties involved in generating free charge carriers through chemical doping. To devise a novel doping platform, the doping capabilities of four designed conjugated polymers (CPs) are quantitatively characterized using an AC Hall-effect device. The resulting carrier density is related to the degree of electronic coupling between the CP repeating unit and 2,3,5,6-tetrafluoro-7,7,8,8-tetracyanoquinodimethane (F4-TCNQ), and doped PIDF-BT provides an outstanding electrical conductivity, exceeding 210 S cm−1, mainly due to the doping-assisted facile carrier generation and relatively fast carrier mobility. In addition, it is noted that a slight increment in the electron-withdrawing ability of the repeating unit in each CP diminishes electronic coupling with F4-TCNQ, and severely deteriorates the doping efficiency including the alteration of operating doping mechanism for the CPs. Furthermore, when PIDF-BT with high doping capability is applied to the hole transporting layer, with F4-TCNQ as the interfacial doping layer at the interface with perovskite, the power conversion efficiency of the perovskite solar cell improves significantly, from 17.4% to over 20%, owing to the ameliorated charge-collection efficiency. X-ray photoelectron spectroscopy and Kelvin probe analyses verify that the improved solar cell performance originates from the increase in the built-in potential because of the generation of electric dipole layer.
Keywords: Charge collection efficiency; Electric dipole layer; Electrical conductivity; Electron-withdrawing ability; Free charge carriers; Hole transporting layers; Power conversion efficiencies; Solar cell performance; conducting polymers; conjugated polymers; doping; molecular electronics; solar cells